2012
DOI: 10.1038/nature11474
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared background anisotropies from diffuse intrahalo light of galaxies

Abstract: Unresolved anisotropies of the cosmic near-infrared background radiation are expected to have contributions from the earliest galaxies during the epoch of reionization and from faint, dwarf galaxies at intermediate redshifts. Previous measurements were unable to pinpoint conclusively the dominant origin because they did not sample spatial scales that were sufficiently large to distinguish between these two possibilities. Here we report a measurement of the anisotropy power spectrum from subarcminute to one-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
238
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(252 citation statements)
references
References 29 publications
13
238
1
Order By: Relevance
“…Collaboration 2013; Biteau & Williams 2015). (Kashlinsky et al , 2007aCooray et al 2012b), HST/NICMOS (Thompson et al 2007a,b) and AKARI/IRC (Matsumoto et al 2011;Seo et al 2015), confirm a mutually consistent isotropic signal above the noise extending out to ∼1…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Collaboration 2013; Biteau & Williams 2015). (Kashlinsky et al , 2007aCooray et al 2012b), HST/NICMOS (Thompson et al 2007a,b) and AKARI/IRC (Matsumoto et al 2011;Seo et al 2015), confirm a mutually consistent isotropic signal above the noise extending out to ∼1…”
Section: Introductionmentioning
confidence: 83%
“…This is in part because of the lack of a robust redshift determination of the signal and because recent models of early galaxy populations z 6 have failed to produce sufficient CIB fluctuation power (Fernandez et al 2012;Cooray et al 2012a;Yue et al 2013a). This has motivated alternative hypotheses for their origin, such as in a diffuse intrahalo light at low/intermediate-z (Cooray et al 2012b;Zemcov et al 2014). At the same time, it was suggested that accretion by direct collapse black holes (DCBH) at high-z can provide an explanation which also fully accounts for the CIB×CXB signal (Yue et al 2013b).…”
Section: The Unresolved Cib Fluctuations Measured With Spitzer/iracmentioning
confidence: 99%
“…The signal tends to rise above the shot noise towards intermediate and large scales, with an amplitude that is thought to be inconsistent with faint galaxies (Helgason et al 2012) (H12 hereafter) and other foregrounds such as Diffuse Galactic Light (DGL) or Zodiacal Light (ZL) (Pyo et al 2012;Tsumura et al 2013a,b;Arai et al 2015;Arendt et al 2016). This has often been referred to as the "excess" NIRB fluctuations, the origin of which is currently debated (Kashlinsky et al 2007b;Fernandez et al 2010;Cooray et al 2012;Yue et al 2013;Zemcov et al 2014;Gong et al 2015;Helgason et al 2016;Yue et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Foreground diffuse components, such as zodiacal light, diffuse Galactic light, and unresolved faint galaxies at low redshift, are all candidates for inducing spatial structures in the near-infrared sky. In addition, intrahalo light (IHL; Cooray et al 2012) and first stars in the early universe are also candidates. Seo et al (2015) investigated spatial structures in the NEP deep field using mosaicked images in the bottom panel of Figure 1.…”
Section: Discussionmentioning
confidence: 99%